Temperature and moisture distributions in a moist spherical capillary-porous body - A new approach - Pandey R.N.; Pandey S.K.; Mikhailov M.D. (My University, 2025)
A novel technique, which is a combination of the Laplace transform and matrix calculus, is employed to obtain the exact solutions of the linearized Luikov system of coupled heat and moisture transport equations in a spherical capillary porous body addressed to specified initial and boundary conditions. It is shown that under certain restrictions, in the case of convective-type boundary conditions, the transcendental equation yields a countable number of complex conjugate roots. Here, a new computational scheme is employed, which evaluates real as well as a countable number of pairs of complex conjugate roots. A set of benchmark results is generated for the Luikov drying model, and in a way better than the alternative solutions proposed by Lobo et al. [19] for linear problems. Copyright © 1999 John Wiley & Sons, Ltd.